Determinants of Internet Financial Reporting in Sri Lanka - Inthusha, K.; Kajananthan, R. (Rajarata University of Sri Lanka, 2021)
Internet financial reporting is an emerging form of reporting channel as well as voluntary in nature. There are no specific prescribed regulations, hence, there are disparities of internet financial reporting practices among companies regardless of the nature of businesses as well as countries. Much entities-related information is reported for the better decision making of its stakeholders. This investigation aims to examine the potential factors that may affect the level of internet financial reporting of Sri Lankan companies. The sample of the study consists of 298 firms listed on Colombo Stock Exchange. In order to investigate the extent of internet financial reporting practices, the website of the companies for the year 2020 were analyzed through content analysis, which was then used to develop an index. Internet financial reporting index is developed weighted sum of disclosures of basic and non-financial information about the bu8siness, users friendly, timeliness, accessibility information, and investors relations information and components of financial information. Firm size, profitability, leverage, and industry types are considered independent variables that influence the companies’ internet financial reporting practices. The finding of this study indicated that firm size and leverage have significant effects on the total score of internet financial reporting levels (F= 15.017; P < 0.05), which predicts 21.8 percent of the variation in the internet financial reporting level. It could be concluded that large firm size has a high intention to disclosure all types of information mainly in investors’ relation information than others. The results are also in line with the agency theory which claims that larger firms will avoid the agency problems by enhancing disclosures of all types of information for their related parties on corporate websites. Further, companies that have high leverage firms are responsible to satisfy the creditors’ needs by publishing reliable information on the websites to ensure the creditors have high confidence in their ability to pay the debts. Future investigation is needed with more other variables in a different context.
Keywords: Firm size; Internet financial reporting; Leverage; Profitability; Website